Comparative Analysis Of Ki Hajar Dewantara's Character Education With John Dewey - Romadhon, Dwi Nanda Akhmad; Sutarni, Nani (Jurnal Pendidikan Karakter, 2025)
Character education is the foundation for human beings as civilized people in society. This study aims to examine the comparative results of character education thinking. The researcher only compares the results of character education thinking, Ki Hajar Dewantara with Jhon Dewey. This research uses a qualitative method by using literature revieu from various literatures such as scientific journals, books, and researches related to the subject matter. This research analyzes the comparative results of the thoughts of these character education figures, which although they have positive differences in their thoughts, are for the advancement of education in Indonesia which creates individuals who are virtuous and have good personalities, are able to think critically, actively, and participate in society. Nevertheless, both agree that character education should be the main focus in the education system in Indonesia in order to create qualified individuals who are able to make a positive contribution to society. Therefore, a joint effort from all parties is needed to strengthen character education in Indonesia to achieve this goal.